Sharia Law: Its Nature, Characteristics and Sources - Yimam, Alyu Abate (Bahir Dar University Journal of Law, 2023)
Sharia can be defined as a divinely inspired legal system that exists within the religious of framework of Islam. Sharia represents two distinct but directly related sets of laws. The first segment consists of theories, principles, and objectives that serve as foundations for the promulgation and interpretation of specific laws. There is an independent discipline devoted to the study of philosophical and juristic principles of Sharia law known as Principles of Islamic Jurisprudence (Usul al-Fiqh). The other part of Sharia is concerned with the regulation and guidance of every day interaction of individuals and society. This part of Sharia espouses detail legal rulings on the worldly matters (Mua’malat) on one hand and set of rules governing ritual matters (Ibadat) on the other. The Mua’malat laws have the objectives of realizing personal and public benefit, ensure peace and wellbeing and prevention of harm and corruption in a society. Sharia has all important attributes of rationality, gradualness and adaptability that are essential for effective governance of human relationships at all times and circumstances. Key Word